EFFECT OF QUALITY OF HUMAN RESOURCES, UTILIZATION OF TECHNOLOGY AND APPLICATION OF SAP ON THE RELIABILITY OF FINANCIAL STATEMENTS WITH INTERNAL CONTROL SYSTEM AS A VARIABLE MODERATION - Neni Nurhayati (SEAN Institute, 2022)
This study aims to determine the effect of the quality of human resources, the use of information technology, and the application of accrual-based government accounting standards on the reliability of village government financial reporting with internal control systems as a moderating variable. This type of research uses quantitative research methods, with a population of 361 villages in Kuningan Regency and a total sample of 190 villages, namely financial officers or treasurers as respondents. The sampling technique used is probability sampling technique. The data collection technique used a questionnaire with data analysis tools in the form of multiple linear regression analysis. The results of this study indicate that the quality of human resources, the use of information technology, internal control systems, organizational commitment, and the application of accrual-based accounting standards together have a positive effect on the reliability of village government financial reporting.